Bamboo - The Miracle Plant Towards Ensuring Environmental Restoration and Job Creation in Nigeria (International Journal of Bamboo and Rattan, 2023)
No doubt, the celebration of World Bamboo Day is of utmost necessity because climate change is one of the biggest dilemmas that the world is facing today. Nowadays, the changes are alarmingly high and the impacts are also strongly felt in Nigeria.The overall objective of this paper is to persuade the federal and state governments, businesses, and stakeholders on the need to invest in bamboo projects and programmes both, as a nature-based solution resource to improving our environment and to giving our teaming unemployed youths an alternative and better means of livelihood.
Keywords: nature-based solution; youths unemployment; World Bamboo Day; climate change